As expressões da modernidade no Brasil: o lugar da arquitetura associada ao termo art déco - Farias, Fernanda de Castro (2018)
Art deco is a nomenclature used to an architectonic production that strives to express modernity in building forefronts through ornament geometrization, presenting decorative elements and singular formal features. This thesis assumes that the production associated with art deco participates in the Brazilian modernization process, and it is spread over the country during the second quarter of the 20th century. However, the modern architecture hegemonical history version does not adequately consider this production. The purpose of this study is to identify this architectonic production dissemination in Brazil and place it in the history of Brazilian architecture through a histographical analysis. This investigation has as its basis the following research resources, divided into four narratives: 1) five books to the canonical historiography version, 2) four books and one mastering dissertation for the recent historiography version, 3) twenty-seven recent academic works regarding the theme, comprising six books, three doctoral theses, seven mastering dissertations, and eleven papers and 4) one historical document, thirty-six volumes of Brazilian cities Encyclopedia, edited by IBGE between 1957 and 1964. According to this analysis and identification of formal elements that characterize the developed production, we developed a map that enables visualizing this architecture extension through the country and allows understanding its academic context. The implication of this work is the possibility of organizing the knowledge about how this architecture is disseminated through the country, identify a stylist unity and to learn the place of this modern production in Brazil.